“No research on a dead planet”: preserving the socio-ecological conditions for academia - Thierry, Aaron; Horn, Laura; von Hellermann, Pauline; Gardner, Charlie J. (Frontiers in Education, 2023)
Emergency declarations, most academics continue to operate according to 'businessas-usual'. However, such passivity increases the risk of climate impacts so severe as to threaten the persistence of organised society, and thus HEIs themselves. This paper explores why a maladaptive cognitive-practice gap persists and asks what steps could be taken by members of HEIs to activate the academy. Drawing on insights from climate psychology and sociology, we argue that a process of 'socially organised denial' currently exists within universities, leading academics to experience a state of 'double reality' that inhibits feelings of accountability and agency, and this is selfreenforcing through the production of 'pluralistic ignorance'. We further argue that these processes serve to uphold the cultural hegemony of 'business-as-usual' and that this is worsened by the increasing neo-liberalisation of modern universities. Escaping these dynamics will require deliberate efforts to break taboos, through frank conversations about what responding to a climate emergency means for universities' -and individual academics'core values and goals. * This search was for papers on any topic under the theme of environmental issues